Short-chain fatty acids as key mediators of the microbiota–gut–brain axis in chronic cerebral hypoperfusion: mechanisms and therapeutic - Junchen Si; Peijian Wang; Zhongchen Li; Jiheng Hao; Jiyue Wang; Liyong Zhang (Molecular Medicine, 2026)
Abstract Chronic cerebral hypoperfusion (CCH) is an important contributor to vascular cognitive impairment and neurodegenerative disorders, characterized by neuronal injury, blood–brain barrier (BBB) disruption, neuroinflammation, mitochondrial dysfunction, and synaptic impairment. Increasing evidence suggests that the microbiota–gut–brain axis plays a crucial role in ischemic brain injury. CCH is associated with gut microbiota dysbiosis, intestinal barrier dysfunction, and reduced production of microbiota-derived short-chain fatty acids (SCFAs), which may be linked to cognitive decline through bidirectional gut–brain communication. This review summarizes the mechanisms potentially involved in CCH-related neurological damage and highlights the potential neuroprotective effects of SCFAs, including regulation of neuroinflammation, BBB integrity, mitochondrial homeostasis, neuronal apoptosis, and synaptic plasticity. Furthermore, potential microbiota-targeted therapeutic strategies, such as fecal microbiota transplantation, probiotics/prebiotics, and SCFA supplementation, are discussed. Targeting gut microbiota-derived SCFAs may represents a promising approach for improving CCH-associated cognitive impairment, although further clinical validation is required.